2014
DOI: 10.1182/blood-2013-04-497842
|View full text |Cite
|
Sign up to set email alerts
|

A 1-year randomized controlled trial of deferasirox vs deferoxamine for myocardial iron removal in β-thalassemia major (CORDELIA)

Abstract: Key Points In β-thalassemia major patients with severe iron burden, deferasirox was noninferior to deferoxamine for myocardial iron removal. The ejection fraction was stable during treatment for both deferasirox and deferoxamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
90
6
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 108 publications
(106 citation statements)
references
References 34 publications
6
90
6
4
Order By: Relevance
“…Consideration of the rate of myocardial iron removal is important, since the implications and subsequent treatment of patients with myocardial T2* values of 10 to 20 ms differ from those with values <10 ms, who are at a greater risk of heart failure. Even so, the present study demonstrated that patients could normalize their myocardial T2* to >20 ms; achieved by a greater proportion of patients at 24 months than at 12 months in both deferasirox (24.3 versus 17.6%) and DFO patients (17.2 versus 6.2%) [8]. Importantly, 72.7% of patients treated with deferasirox and 54.5% of patients treated with DFO improved from severe (T2* <10 ms) to mild-to-moderate (T2* 10-20 ms) myocardial iron overload after 24 months-a clinically important increase since the relative risk of heart failure in patients with myocardial T2* <10 ms compared with T2* >10 ms has been shown to be significantly higher (relative risk 160 [95% CI 39-653]) [20].…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…Consideration of the rate of myocardial iron removal is important, since the implications and subsequent treatment of patients with myocardial T2* values of 10 to 20 ms differ from those with values <10 ms, who are at a greater risk of heart failure. Even so, the present study demonstrated that patients could normalize their myocardial T2* to >20 ms; achieved by a greater proportion of patients at 24 months than at 12 months in both deferasirox (24.3 versus 17.6%) and DFO patients (17.2 versus 6.2%) [8]. Importantly, 72.7% of patients treated with deferasirox and 54.5% of patients treated with DFO improved from severe (T2* <10 ms) to mild-to-moderate (T2* 10-20 ms) myocardial iron overload after 24 months-a clinically important increase since the relative risk of heart failure in patients with myocardial T2* <10 ms compared with T2* >10 ms has been shown to be significantly higher (relative risk 160 [95% CI 39-653]) [20].…”
Section: Discussionmentioning
confidence: 50%
“…Detailed patient inclusion and exclusion criteria have been reported previously [8]. Briefly, patients eligible for enrollment at baseline were male or female, aged !10 years with beta thalassemia major, sideroblastic anemia, myelodysplastic dysplastic syndromes (low/intermediate-1) or Diamond-Blackfan anemia; however, only patients with beta thalassemia major fulfilled all inclusion criteria and were enrolled.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations